Audidt Sistem Informasi Portal Akademik Menggunakan Framework Cobit 4.1 Domain ME Pada Universitas Swasta Di Jakarta Barat - Johanes Andry; Lili Tresha; Michelle Disa Widjaja; Vania Christy; Julia Loisa (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
The development of information technology in various aspects of human life makes information technology an important thing in a company or institution that is used in many ways. Private University in West Jakarta is a private educational institution that uses information technology in its operational activities. Especially during a pandemic where lectures are held online, students learn through the student academic portal website which manages all class schedules, attendance and exams. In this study, researchers will audit the system on the academic portal of private university students in West Jakarta using the COBIT 4.1 framework in the ME (Monitoring and Evaluation) domain, whether the system processes that have been running so far are going well and effectively, so that all audit analysis is carried out. carried out in accordance with the existing standards in the framework.